Constitutionalizing Canadian private international law – 25 years since Morguard - Blom, Joost (Journal of Private International Law, 2017)
Because of its structuring function, private international law tends to be given a status distinct from the ordinary rules of domestic law. In a federal system, private international law of necessity implicates some aspects of the constitution. In a series of cases beginning in 1990 the Supreme Court of Canada has engaged in a striking reorientation of Canadian private international law, premised on a newly articulated relationship between private international law and the Canadian constitutional system. This constitutional dimension has been coupled with an enhanced notion of comity. The new dynamic has meant that changes in private international law that were initially prompted by constitutional considerations have gone further than the constitutional doctrines alone would demand. This paper traces these developments and uses them to show the challenges that the Supreme Court of Canada has faced since 1990 in constructing a relationship between Canada’s constitutional arrangements and its private international law. The court has fashioned the constitutional doctrines as drivers of Canadian private international law but its own recent jurisprudence shows difficulties in managing that relationship. The piece concludes with lessons to be learned from the experience of the last 25 years.
_eprint: https://doi.org/10.1080/17441048.2017.1355081